2021
DOI: 10.1017/jfm.2020.1176
|View full text |Cite
|
Sign up to set email alerts
|

Much faster heat/mass than momentum transport in rotating Couette flows

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
(157 reference statements)
2
6
0
Order By: Relevance
“…2016; Huang et al. 2019; Huang, Xia & Chen 2020; Brethouwer 2021) and sheared Rayleigh–Bénard convection (Blass et al. 2020, 2021) may provide some evidence for the validity of our conjectures.…”
Section: Numerical Results and Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…2016; Huang et al. 2019; Huang, Xia & Chen 2020; Brethouwer 2021) and sheared Rayleigh–Bénard convection (Blass et al. 2020, 2021) may provide some evidence for the validity of our conjectures.…”
Section: Numerical Results and Discussionsupporting
confidence: 55%
“…The results of rotating plane Couette flow () at five different are from Huang et al. (2020) (without heat transfer data) and Brethouwer (2021, 2023), while those of sheared Rayleigh–Bénard convection () at six different are from Blass et al. (2020).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the different monotonicity in their mean velocity profiles. Furthermore, heat transfer in RPCF was also studied through DNS by Brethouwer (2021, 2023), and they reported that the classical Reynolds analogy is invalid in RPCF with heat transfer, which can be successfully explained with the thermal analogy.…”
Section: Introductionmentioning
confidence: 99%
“…enabling the favourable breakdown of the Reynolds analogy. Although the optimized shear flows in those studies were driven by an arbitrary body force, it was demonstrated that a heat transfer rate higher than skin friction can be realized by Coriolis force for shear flows subjected to system rotation (Brethouwer 2021) and buoyancy force for mixed convection with unstable stratification (Pirozzoli et al. 2017).…”
Section: Introductionmentioning
confidence: 99%